Assessment of exposure to nickel intake with selected cereal grains and cereal-based products - Monika Mania; Małgorzata Rebeniak; Oksana Orshulyak; Jacek Postupolski (Roczniki Panstwowego Zakladu Higieny, 2020)
Background. Cereal grains and their products are among the basic components of the diet all over the world. Their consumption varies depending on the dietary habits in each country. Apart from ingredients valuable from a health point of view, these products can also be a source of contaminants. The European Food Safety Authority (EFSA) included these foodstuffs in the group of main contributors to the dietary exposure to nickel by different groups of the population. Objective. The aim of the studies was to determine the nickel content in cereal grains and selected cereal products commercially available in Poland and to assess the exposure of consumers to nickel intake with these foodstuffs. Material and methods. A total of 56 samples of cereal grain and cereal products from trade were tested. Nickel content was determined after microwave mineralization of the samples by atomic absorption spectrometry with a graphite furnace atomization (GFAAS). The estimated exposure for the different groups of the population was assessed and compared with the Tolerable Daily Intake (TDI) value established by the European Food Safety Authority based on an updated risk assessment at 13 μg/kg body weight (b.w.) per day. Results. The mean (MB) and 95th percentile (MB) nickel content in investigated samples of cereal grains and their products were 0.66 mg/kg and 1.93 mg/kg. The mean content of Ni in the analyzed samples of grains was 1.16 mg/kg. Obtained results in this group of products ranged from 0.10 mg/kg for rye to 4.80 mg/kg for millet. In the group of grain products, the mean (MB) concentration of nickel was 0.61 mg/kg (95th percentile (MB) 1.84 mg/kg). The highest nickel level was determined in the samples of bran, groats, and flakes compared to other grain-based products. The highest content of Ni in the group of cereal products was found in the samples of roasted buckwheat 1.81 mg/kg and oat flakes 2.53 mg/kg. Significantly lower nickel content was observed in barley groats as well as for pasta and flour. The estimated average exposure of adults and children to nickel intake with grains and grain-based products ranged from 1.1% to 13.4% of TDI and it does not pose a health risk for consumers. Conclusions. Based on the obtained results, it was found that the nickel content in the tested samples of cereals and their products does not pose a health risk, even though the contamination of individual samples was significant.